South Asian Countries in Regional Integration Perspective: A Critical Review - Sultana, Sharmin; Asrat, Jumana (Journal of Business and Technology (Dhaka), 2015)
This article focuses on regional integration among the eight South Asian countries i.e. Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. This study attempts to undertake an in-depth assessment of the potential of South Asian Free Trade Agreement (SAFTA) in South Asian Association for Regional Cooperation (SAARC) countries. The study is based on secondary data collected from different reliable sources. SAFTA can be a strong source of economic development and it can also enhance socio-economic opportunities throughout the region. Larger and economically stronger countries can achieve better bargaining power on trade negotiations by utilizing existing competitive advantages and regional expertise of the region as a unit. This approach can also help less developed countries to develop their economies and also can ensure the best possible use of the existing resources. Journal of Business and Technology (Dhaka) Vol.9(2) 2014; 43-59